More Automation and Less Cognitive Control of Imagined Walking Movements in High- Versus Low-Fit Older Adults - Godde, Ben; Voelcker-Rehage, Claudia (Frontiers in Aging Neuroscience, 2010)
Using motor imagery, we investigated brain activation in simple and complex walking tasks (walking forward and backward on a treadmill) and analyzed if the motor status of older adults influenced these activation patterns. 51 older adults (64-79 years of age) were trained in motor execution and imagery and then performed the imagination task and two control tasks (standing, counting backward) in a horizontal position within a 3T MRI scanner (first person perspective, eyes closed). Walking backward as compared to walking forward required larger activations in the primary motor cortex, supplementary motor area, parietal cortex, thalamus, putamen, and caudatum, but less activation in the cerebellum and brainstem. Motor high-fit individuals showed more activations and larger BOLD signals in motor-related areas compared to low-fit participants but demonstrated lower activity in the dorsolateral prefrontal cortex. Moreover, parietal activation in high-fit participants remained stable throughout the movement period whereas low-fit participants revealed an early drop in activity in this area accompanied by increasing activity in frontal brain regions. Overall, walking forward seemed to be more automated (more activation in cerebellum and brainstem), whereas walking backward required more resources, e.g. for visual-spatial processing and sensorimotor control. Low-fit subjects in particular seemed to require more cognitive resources for planning and controlling. High-fit subjects, on the contrary, revealed more movement automation and a higher “attention span.” Our results support the hypothesis that high fitness corresponds with more automation and less cognitive control of complex motor tasks, which might help to free up cognitive resources.